Remote monitoring of oxygen saturation in individuals with COVID-19 pneumonia. Issue 2 (13th August 2020) - O'Carroll, Orla; MacCann, Rachel; O'Reilly, Aoife; Dunican, Eleanor M.; Feeney, Eoin R.; Ryan, Silke; Cotter, Aoife; Mallon, Patrick W.; Keane, Michael P.; Butler, Marcus W.; McCarthy, Cormac
Coronavirus disease 2019 (COVID-19), an illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, has spread rapidly worldwide, resulting in significant mortality and placing major strain on healthcare systems. Although the clinical course is variable, one in five patients will require hospitalisation for management, with older age and the presence of comorbidities increasing the risk of more severe disease [1–3]. The median time from first onset of symptoms to development of acute respiratory distress syndrome in those who progress to severe disease is estimated to be 8.0 days [4]. Remote monitoring of oxygen saturation in cases of COVID-19 pneumonia may facilitate discharge, relieving burden on bed demand and allowing safe follow-up for this disease in which the sequelae are unknown https://bit.ly/3cTXnZU